Predictors of Response to 24-Week Telaprevir-Based Triple Therapy for Treatment-Naïve Genotype 1b Chronic Hepatitis C Patients. (14th August 2014) - Abe, Hiroshi; Tsubota, Akihito; Shimada, Noritomo; Atsukawa, Masanori; Kato, Keizo; Takaguchi, Koichi; Asano, Toru; Chuganji, Yoshimichi; Sakamoto, Choitsu; Toyoda, Hidenori; Kumada, Takashi; Ide, Tatsuya; et al.
Abstract : We evaluated the genetic variation in rs8099917, substitutions in core amino acid (aa) 70, and the number of aa substitutions in the interferon sensitivity-determining region (ISDR) on the prediction of sustained virological response (SVR) in treatment-naïve hepatitis C virus (HCV) genotype 1b (G1b) patients. This multicenter study involved 150 Asian treatment-naïve patients infected with HCV G1b who received 12 weeks of telaprevir in combination with 24 weeks of peginterferon- α -2b and ribavirin. The baseline and treatment-related factors potentially associated with SVR were determined by multivariate logistic regression analysis. Virological response was analyzed on an intent-to-treat basis. Cessation of the therapy due to adverse effects occurred in only 2 patients, who discontinued the trial at 10 weeks and at 2 weeks due to cerebral infarction and renal impairment, respectively. Among the 150 patients in whom the final virological response was determined, only genotype TT in rs8099917 was identified as a pretreatment predictor ( P = 7.38 × 10 −4 ). Achievement of a rapid virological response (RVR), defined as undetectable HCV RNA at week 4 of treatment, was identified as an after-starting-treatment predictor ( P = 2.47 × 10 −5 ). However, neither a substitution in core aa 70 nor the number of substitutions in the ISDR affected treatment outcome.